The Internalization of the Qur'an Version to Build Students' Character in the Post-Pandemic Covid-19 Era: Pasbiker E-Book to Develop Students’ English Vocabulary and Grammar - Niken Kencon Ungu; Chairani Astina (IJLECR (International Journal of Language Education and Cultural Review), 2022)
Building character can be done by internalizing the Qur'anic verses so that any religion can still take the noble values in it. The objectives of this study are to increas students' competence, especially in terms of mastery and improvement of vocabulary and understanding of grammar gradually through the "Keledai Cerdik" technique based on subject matter that has been internalized with verses of the Qur'an and to give brief information about how the PASBIKER book works to increase vocabulary and mastery of grammar. This research method used the research and mevelopment method through the questionnaires and test. The research result found that both the mastery of vocabulary, grammar, and the values taught on the internalization of the verses of the Qur'an will be documented in detail in a book called "Polis Asuransi Berbahasa Inggris Keledai Cerdik (PASBIKER)”. It gives positive impacts on studets’ vocabulary and grammar mastery. It is suggested to consider the students’ needs in developing the material.